Critical failure and success factors of Information Technology projects - Sidortsov, Victor (fi=Turun yliopisto|en=University of Turku|, 2017)
Information Technology (IT) is a rapidly evolving industry affecting more and more aspects of everyday life. To reap the benefits enabled by IT, organizations adopt a project approach. Projects involving application of IT are known as IT projects. As a rule, such projects require substantial financial and human resources. Yet research evidence, for instance, CHAOS reports, demonstrates that the success rate of IT projects remains fairly low. Given the magnitude of investments placed into the field, this situation has to be improved. Thus, this dissertation aims to identify and classify specific factors of IT project work that would significantly decrease the probability of its failure and increase the chance of its success. Accordingly, the first research question is formulated as “What are the critical factors of success and failure in IT projects?” and the second one as “How do critical factors correlate with each other? In particular, which factors are only critical to success and which ones only to failure? What are the factors critical both to success and failure?” This research has a qualitative theoretical drive. An extensive literature review was performed to extract critical success factors (CSFs) and critical failure factors (CFFs) of IT projects. These factors were later supplemented by CSFs and CFFs identified through the series of semi-structured interviews with project managers and IT specialists. The validity of the critical factors from the literature was verified by the interviewees. As a result of the interviews analysis, the following nine top-level critical factors grouping individual critical factors emerged: project management, project team, business analysis, technical implementation, organization, stakeholder, supplier and product. Subsequently, the identified CSFs and CFFs were compared to classify them into factors critical to both success and failure, factors critical to failure only and factors critical to success only. The research outcomes possess both practical and theoretical value. Thus, in order to maximize the probability of success and minimize the likelihood of failure of an IT project, management should ensure satisfactory results in the areas of project work that correspond to critical factors with a bidirectional influence on success and failure. These factors are those identified as critical to both success and failure. Secondarily, management should concentrate on the factors critical to failure only – to reduce the probability of project failure – and finally, on the factors critical to success only – to enhance the chance of success. Project managers could use these factors as a checklist to attend throughout a project. As for the theoretical value, this dissertation enriches the literature on IT project success and failure by integrating both CSFs and CFFs to show not only factors critical to success but a full picture of critical factors. The developed classification also enables a new view on critical factors through the prism of the direction of their effect on success and failure.